Ответ(ы) на вопрос:
[latex]\frac{(-81)^{-5}\cdot 27^{-3}}{9^{-15}}=\frac{-9^{-5}\cdot 9^{-5}\cdot 9^{-3}\cdot 3^{-3}}{3^{-15}\cdot 3^{-15}}=-\frac{3^{-5}\cdot 3^{-5}\cdot 3^{-5}\cdot 3^{-5}\cdot 3^{-3}\cdot 3^{-3}\cdot 3^{-3}}{3^{-15}\cdot 3^{-15}}=\\\\ =-\frac{3^{(-5)\cdot 4+(-3)\cdot 3}}{3^{-15+(-15)}}=-\frac{3^{-29}}{3^{-30}}=(-3)^{-29-(-30)}=(-3)^{1}=-3[/latex]
!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
Не нашли ответ?
Похожие вопросы